The GLP-1 receptor agonist exenatide improves recovery from spinal cord injury by inducing macrophage polarization toward the M2 phenotype - Noguchi, Toshihiro; Katoh, Hiroyuki; Nomura, Satoshi; Okada, Keiko; Watanabe, Masahiko (Frontiers in Neuroscience, 2024)
Although a wide variety of mechanisms take part in the secondary injury phase of spinal cord injury (SCI), inflammation is the most important factor implicated in the sequelae after SCI. Being central to the inflammation reaction, macrophages and their polarization are a topic that has garnered wide interest in the studies of SCI secondary injury. The glucagon-like peptide 1 (GLP-1) receptor agonist exenatide has been shown to enhance the endoplasmic reticulum stress response and improve motor function recovery after spinal cord injury (SCI). Since exenatide has also been reported to induce the production of M2 cells in models of cerebral infarction and neurodegenerative diseases, this study was conducted to examine the effects of exenatide administration on the inflammation process that ensues after spinal cord injury. In a rat contusion model of spinal cord injury, the exenatide group received a subcutaneous injection of 10 μg exenatide immediately after injury while those in the control group received 1 mL of phosphate-buffered saline. Quantitative RT-PCR and immunohistochemical staining were used to evaluate the effects of exenatide administration on the macrophages infiltrating the injured spinal cord, especially with regard to macrophage M1 and M2 profiles. The changes in hind limb motor function were assessed based on Basso, Beattie, Bresnahan locomotor rating scale (BBB scale) scores. The improvement in BBB scale scores was significantly higher in the exenatide group from day 7 after injury and onwards. Quantitative RT-PCR revealed an increase in the expression of M2 markers and anti-inflammatory interleukins in the exenatide group that was accompanied by a decrease in the expression of M1 markers and inflammatory cytokines. Immunohistochemical staining showed no significant difference in M1 macrophage numbers between the two groups, but a significantly higher number of M2 macrophages was observed in the exenatide group on day 3 after injury. Our findings suggest that exenatide administration promoted the number of M2-phenotype macrophages after SCI, which may have led to the observed improvement in hind limb motor function in a rat model of SCI.